Spectral refining of organic photodiodes: Via chemical doping: From analyses to applications - Kang, Mingyun; Ko, Seong Min; Kim, Juhee; Hassan, Syed Zahid; Jee, Dong Woo; Chung, Dae Sung (Materials Horizons, 2020)
Precise and facile junction engineering of organic photodiodes (OPDs) via chemical doping is demonstrated. This method is different from previous narrowband detection strategies, in that only the depletion region width, not the overall thickness of the active layer, is controlled to realize thin-film narrowband-selective OPDs for noise-tolerant optical sensors. This journal is
Keywords: Active Layer; Chemical doping; Depletion region; Narrow bands; Noise-Tolerant; Organic photodiodes